APLICAÇÃO DO MÉTODO DE SOLUÇÃO DE PROBLEMAS A3 PARA O AUMENTO DE PRODUTIVIDADE EM UM CALL CENTER : APPLICATION OF A3 PROBLEM SOLVING TECHNIQUE TO INCREASE PRODUCTIVITY IN A CALL CENTER - Donato, Jhordana Silva (2022)
Lean associated with quality tools and problem solving methodology has driven companies in the search for productivity as a strategic differential. Not investing more resources, manpower and training, but also analyzing the problems they are working on and how these can be solved in a lead time manner. Through the A3 Problem Solving tool and the PDCA method, it is possible to investigate causes-effects and causes of problems, seeking to mitigate problems, increasing profitability. This case study used this objective, which goes through the stages of planning, execution, verification and action, and was able to achieve the goal of one of the main tools of the process, the Average Service Time (TMA), which has a goal of six minutes and 50 seconds, reflecting directly on the productivity of the operation. Applied in a process of opening service in a call center, located in the city of Vila Velha/ES, the company has an average of 200 service agents. With the application of the methodology, there was a gain of two minutes and 14 seconds in the call, in addition to an avoided cost of 0.27 cents per call, totaling, on average, 16 thousand reais in a period of one month.